2014
DOI: 10.1016/j.ijid.2014.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug carbapenem-resistant Klebsiella pneumoniae infection carrying the OXA-48 gene and showing variations in outer membrane protein 36 causing an outbreak in a tertiary care hospital in Riyadh, Saudi Arabia

Abstract: This is probably the first reported outbreak of multidrug/carbapenem-resistant Klebsiella infection involving the OXA-48 gene from Saudi Arabia. Although the presence of ESBLs such as OXA, CTX-M, TEM, and SHV are predictable reasons for resistance, variations in the Omp-36 gene might also have precipitated this phenomenon. Disruption of the Omp-36 sequence by large insertional elements, the insertion of two amino acids in a very crucial part of this protein, and the presence of a premature stop codon in one is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
47
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 38 publications
9
47
3
Order By: Relevance
“…In our study, we found 81.9% of the NDM-1 isolates co-expressed different ESBL and/or AmpC genes, exhibiting a complex β-lactamase background that was consistent with previous studies [2526]. The SHV-type ESBL gene was the most prevalent among the isolates, followed by the CTX-M-type, which is in agreement with two previous results [2728]. Furthermore, the identification of DHA-1 as the predominant AmpC in the CRKP isolates is similar to the recent findings in China [29].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found 81.9% of the NDM-1 isolates co-expressed different ESBL and/or AmpC genes, exhibiting a complex β-lactamase background that was consistent with previous studies [2526]. The SHV-type ESBL gene was the most prevalent among the isolates, followed by the CTX-M-type, which is in agreement with two previous results [2728]. Furthermore, the identification of DHA-1 as the predominant AmpC in the CRKP isolates is similar to the recent findings in China [29].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, bla OXA‐48 gene was detected in 9/24 (37.5%) of the resistant isolates; however, Abdallah et al, did not detect it at all in Egypt . Iraz et al, have reported bla OXA‐48 gene with a lower percentage (13%); however Zaman et al, detected bla OXA‐48 gene with a percentage (100%) in Saudi Arabia . The bla VIM‐1 gene was detected in 6/24 (25%) of our isolates, and another Egyptian study also has detected bla VIM‐1 gene amongst K pneumoniae isolates but with a lower percentage (7%) .…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, the ST29 was the predominant ST of carbapenem-resistant K . pneumoniae isolates in Saudi Arabia 35 . The ST15, ST17, ST54, and ST107 isolates producing ESBL, DHA-1, KPC-2 or NDM-1metallo-β-lactamase have been found in Taiwan, China and other various geographic areas in the world 3642 .…”
Section: Discussionmentioning
confidence: 99%